YB‐1 orchestrates onset and resolution of renal inflammation via IL10 gene regulation. Issue 12 (30th June 2017) - Wang, Jialin; Djudjaj, Sonja; Gibbert, Lydia; Lennartz, Vera; Breitkopf, Daniel M.; Rauen, Thomas; Hermert, Daniela; Martin, Ina V.; Boor, Peter; Braun, Gerald S.; Floege, Jürgen; Ostendorf, Tammo; et al.
Abstract: The Y‐box‐binding protein (YB)‐1 plays a non‐redundant role in both systemic and local inflammatory response. We analysed YB‐1‐mediated expression of the immune regulatory cytokine IL‐10 in both LPS and sterile inflammation induced by unilateral renal ischaemia–reperfusion (I/R) and found an important role of YB‐1 not only in the onset but also in the resolution of inflammation in kidneys. Within a decisive cis ‐regulatory region of the IL10 gene locus, the fourth intron, we identified and characterized an operative YB‐1 binding site via gel shift experiments and reporter assays in immune and different renal cells. In vivo, YB‐1 phosphorylated at serine 102 localized to the fourth intron, which was paralleled by enhanced IL‐10 mRNA expression in mice following LPS challenge and in I/R. Mice with half‐maximal expression of YB‐1 ( Yb1 +/− ) had diminished IL‐10 expression upon LPS challenge. In I/R, Yb1 +/− mice exhibited ameliorated kidney injury/inflammation in the early‐phase (days 1 and 5), however showed aggravated long‐term damage (day 21) with increased expression of IL‐10 and other known mediators of renal injury and inflammation. In conclusion, these data support the notion that there are context‐specific decisions concerning YB‐1 function and that a fine‐tuning of YB‐1, for example, via a post‐translational modification regulates its activity and/or localization that is crucial for systemic processes such as inflammation.